Psychosocial problems and support for disaster medical assistance team members in the preparedness, response and recovery phases of natural hazards resulting in disasters: A scoping review - Zahos, Helen; Crilly, Julia; Ranse, Jamie (Australasian emergency care, 2022)
Clinicians responding to disasters are at risk of experiencing psychosocial problems that can negatively impact them during, upon their return and years after the deployment. Clinicians often respond to disasters as members of organised Disaster Medical Assistance Teams (DMATs). The aim of this paper was to review and synthesise the literature regarding psychosocial problems and support provided to medical personnel in the preparedness, response, and recovery phases of a disaster. A comprehensive search for literature was conducted using four databases: EMBASE; CINAHL; MEDLINE; and PsychInfo. Medical Subject Heading and key terms used in the search included: Disasters; First Responder; Disaster Medical Assistance Team (DMAT); Post-Traumatic Stress Disorder. Psychosocial problems were identified amongst DMAT members in all phases (preparedness, response and recovery) of disaster assistance. These ranged from pre-existing stress and anxiety to Post-Traumatic Stress Disorder. Psychosocial support was mostly reported in the recovery phase of the disaster deployment. A range of strategies exist to support psychosocial problems DMAT members experience, however, these tend to focus on the recovery phase of deployment with limited focus on preparedness and response phases. Further research is required to identify, implement, and evaluate short and long term psychosocial support needs and strategies for DMAT members in all phases of a disaster deployment.